Agglomeration effects and location choice of Japanese electronics firms in China: the case of provincial data - Suminori Tokunaga,; Shaosheng Jin, (Penerbit Universiti Kebangsaan Malaysia, 2007)
This article examines the hypothesis related to the role of agglomeration efects on location choice behavior of Japanese elecrronics firms in China. According to Krugman (1991), Fujita and Krugman (1995), Fujita, Krugman, and Venables (1 999), agglomeration efJects play an important role on location choice behavior. Using the data of Cyugoku Sinsyutsu Kigyou Zchiran 2003 - 2004 (Japanese enterprises investment in China 2003 - 2004), we estimate a location choice model of Japanese electronics f i m using market potential, industrial agglomeration, and traditional factors such as wage, infrastructure, andpolicy incentives as explanatory variables. The result of this estimation shows that the agglomeration effects play an important role on location choice behavior of the Japanese electronics firms in China.